Bunga Bank Dan Riba: Tinjauan Fiqih Muamalah - Akhfah, Akfah Zakiah Jamilah; Ajeung, Ajeung Syilva Syara Noor Silmi Sudrajat; Agung, Agung Wildan Azizi (STAI Al-Mas'udiyah, 2023)
This research discusses usury and bank interest from an Islamic perspective. This research found that the issue of usury and bank interest is still something that is still being debated, some say that bank interest and usury are the same and some say that bank interest is not usury from a legal perspective. This research is research that uses descriptive literature analysis methods. This method provides an overview or explanation of an object that is the focus of research, namely by collecting data, compiling or clarifying it, compiling and interpreting it as well as collecting several references from the books of classical scholars, books, journals, theses, dissertations and others. related to the research object. The term bank interest, as explained in the previous discussion, in the review of muamalah jurisprudence will explain the reasons or illat of the law that usury is prohibited, therefore usury is prohibited because of two things 1). Because of injustice, namely disproportionate profits. In fact, this excess is not because of the prohibition of usury, but because of the element of injustice. 2). Due to exploitation of basic needs or gharar, there is high uncertainty and speculation. So the current view is that flowers are not forbidden as long as they do not contain the two elements above.